Penentuan kedalaman zona degradasi pada lereng highwall di PT putra karya borneo - Natasya Amanda Putri; Tommy Trides; Revia Oktaviani; Albertus Juvensius Pontus; Rety Winonazada (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
lope stability in open-pit mining is a critical aspect influenced by the geotechnical conditions of slope-forming materials, particularly the presence of a degradation zone. This study aims to determine the depth of the degradation zone or Fully Disturbed Limit (FDL) and to analyze its role in the stability of the highwall slope at Pit North, PT Karya Putra Borneo. The research employs a quantitative approach using secondary data, including slope geometry and geotechnical parameters, combined with slope modeling using Slide 6.0 software. The depth of the degradation zone is determined based on a disturbance factor (D) value of 0.7, representing mechanical excavation methods. The results indicate that the degradation zone extends to a depth of approximately 3.9 meters from the slope surface, forming a relatively weaker layer compared to the underlying material. This zone has the potential to act as a weak plane that controls slope failure mechanisms. Therefore, the depth and position of the degradation zone are key factors that must be considered in slope stability analysis to support safer and more effective slope design in open-pit mining.